(untitled) (Baghdad Science Journal, 2022)
The present work involved designing and synthesizing of a series of new. compounds which their molecules are composed from two biologically active components namely sulfamethoxazole or β-lactam containing drugs and cyclic imides. The target new compounds were synthesized by two steps in the first one a series of six bis (N-drug phthalamic acid_4-yl) ketone (1-6) were prepared from the reaction of sulfamethoxazole or β-lactam containing drugs with benzophenone 3, 3′, 4, 4′ -tetracarboxylic dianhydride. In the second step, compounds (1-6) were introduced in dehydration reaction via fusion process producing the target compounds bis (N-drug phthalimidyl-4-yl) ketone (7-12). The antibacterial and antifungal high activities of the prepared compounds (7-12) were tested against (Bacillus subtilis, Klebsiella pneumoniae, Pseudomonas auroginosa and Staphylococcus aurus) and all compounds showed good to high antibacterial activity. However, the maximum inhibition zone was 38 mm against Staphyloccus aurus, 36 mm against Bacillus subtilis, 35 mm against Pseudomonas auroginosa, 28mm against Klebsiella pneumoniae and 19 mm against Rhizosporium fungi.